Renal Denervation Influences Angiotensin II Types 1 and 2 Receptors - Hajaralsadat Hosseini-Dastgerdi; Fatemeh Kharazmi; Ali-Asghar Pourshanazari; Mehdi Nematbakhsh (International Journal of Nephrology)
The sympathetic and renin-angiotensin systems (RAS) are two critical regulatory systems in the kidney which affect renal hemodynamics and function. These two systems interact with each other so that angiotensin II (Ang II) has the presynaptic effect on the norepinephrine secretion. Another aspect of this interaction is that the sympathetic nervous system affects the function and expression of local RAS receptors, mainly Ang II receptors. Therefore, in many pathological conditions associated with an increased renal sympathetic tone, these receptors’ expression changes and renal denervation can normalize these changes and improve the diseases. It seems that the renal sympathectomy can alter Ang II receptors expression and the distribution of RAS receptors in the kidneys, which influence renal functions.